2017
DOI: 10.1177/1076029617705728
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PAI-1 4G/5G Promoter Polymorphism and Its Levels in the Development of Ischemic Stroke in Young Indian Population

Abstract: The plasminogen activator inhibitor-1 (PAI-1) gene has been found to be associated with the pathogenesis and progression of vascular diseases including stroke. A 4G/5G, PAI-1 gene polymorphism has been found to be associated with the plasma PAI-1 levels in different ethnic populations but results are still controversial. The aim of this study was to determine the potential association of 4G/5G polymorphism and plasma PAI-1 levels in the development of ischemic stroke (IS) in young Asian Indians. One hundred pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“… 34 36 Tofler et al 37 prospectively investigated 3203 patients without cardiovascular diseases, and found out that the incidence of cardiovascular events was higher in patients with high PAI-1 levels. Akhter et al 38 reported that the increase in PAI-1 activity and genotype 4G4G were related to the occurrence of ischemic stroke in Indian population. Prabhudesai A et al 39 studies also showed that 4G4G genotype was an independent risk factor for DVT.…”
Section: Discussionmentioning
confidence: 99%
“… 34 36 Tofler et al 37 prospectively investigated 3203 patients without cardiovascular diseases, and found out that the incidence of cardiovascular events was higher in patients with high PAI-1 levels. Akhter et al 38 reported that the increase in PAI-1 activity and genotype 4G4G were related to the occurrence of ischemic stroke in Indian population. Prabhudesai A et al 39 studies also showed that 4G4G genotype was an independent risk factor for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, some discrepancies concerning this polymorphism can be found in the literature. Some of the authors found relations between 4G/ 4G genotype and PAI-1 level 4,5 while others did not. 11 Hindorff et al 12 and Sarecka et al 8 found that the 5G allele of PAI-1 gene but not the 4G allele to be a risk factor for CAD, especially in women.…”
Section: Introductionmentioning
confidence: 93%
“…The study based on young Indian adults (aged up to 45 years) showed that both 4G allele and 4G/4G genotype of PAI-1 gene were associated with increased risk of ischemic stroke. 16 On the other hand, Ranellou et al 17 demonstrated higher frequency of the 4G/5G genotype of the PAI polymorphism in young adults with stroke than in healthy controls. The authors suggested also protective role of 5G/5G genotype.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations